The role of soluble and insoluble gastric fluid components in the pathogenesis of obliterative bronchiolitis in rat lung allografts. (17th December 2015) - Leung, Jason H.; Chang, Jui‐Chih; Bell, Sadé M.; Holzknecht, Zoie E.; Thomas, Samantha M.; Everett, Mary Lou; Parker, William; Davis, R. Duane; Lin, Shu S.
Summary: Repetitive gastric fluid aspirations have been shown to lead to obliterans bronchiolitis (OB), but the component or components of gastric fluid that are responsible are unknown. This study investigates the role of particulates and, separately, soluble material in gastric fluid during the development of OB. Whole gastric fluid (WGF) was collected from male Fischer 344 (F344) rats and separated by centrifugation into particle reduced gastric fluid (PRGF) and particulate components resuspended in normal saline (PNS). Orthotopic left lung transplants from male Wistar–Kyoto rats into F344 rats were performed using a modification of the nonsuture external cuff technique with prolonged cold ischemia. Rats were subjected to weekly aspiration of 0.5 ml/kg of WGF ( n = 9), PRGF ( n = 10), PNS ( n = 9), or normal saline (control, NS; n = 9) for 8 weeks following transplantation. Lung allografts treated with WGF, PRGF, or PNS developed a significantly greater percentage of OB‐like lesions compared with the control. No statistical difference was observed when comparing the fibrosis grades or the percentage of OB lesions of WGF, PRGF, and PNS groups, suggesting that both soluble and insoluble components of gastric fluid can promote the development of aspiration‐induced OB and fibrosis in lung allografts.